Treatment of the patella at the modern stage (a review of literature) - Yevseyenko, Vyacheslav; Zazirniy, Igor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
This article describes techniques of conservative and surgical treatment of lateral patellar instability in its historical aspect and at the modern stage in the development of orthopaedics. The roles of minimally invasive and arthroscopic surgery techniques are characterized. Attention is focused on orthopaedic problems and prospects of their solution.